2013
DOI: 10.1183/09031936.00174612
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophage proteinase/antiproteinase expression in lung function and emphysema

Abstract: Alveolar macrophages play an important role in chronic obstructive pulmonary disease via production of matrix metalloproteinases (MMPs) and cathepsins as well as their inhibitors, tissue inhibitors of metalloproteinases and cystatin C. We hypothesised that expression levels of these molecules by alveolar macrophages at baseline and after stimulation would be influenced by genotype and associated with chronic obstructive pulmonary disease phenotypes.Quantitative PCR and ELISAs/gelatine zymography were used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Increased inflammation correlates with poorer lung function in patients with COPD (Turato et al, 2002;Donaldson et al, 2005;Aronson et al, 2006;Hancox et al, 2007), and small airway fibrosis contributes to airflow restriction through exaggerated tissue contraction, perhaps through the altered balance between fibrotic MMPs and their inhibitors (Hogg et al, 2004;Rennard, 2006;Salazar and Herrera, 2011;Churg et al, 2012;Jankowich and Rounds, 2012). Increases in the levels of alveolar macrophage-associated MMPs negatively correlate with forced expiratory volume in 1 s/forced vital capacity in COPD patients (Ishii et al, 2013). We have shown that depletion of macrophages by clodronate improves transpulmonary and airway resistance as well as dynamic compliance in experimental COPD (Beckett et al, 2013), which possibly occurs through the reduction in MMPs.…”
Section: Bjpmentioning
confidence: 99%
“…Increased inflammation correlates with poorer lung function in patients with COPD (Turato et al, 2002;Donaldson et al, 2005;Aronson et al, 2006;Hancox et al, 2007), and small airway fibrosis contributes to airflow restriction through exaggerated tissue contraction, perhaps through the altered balance between fibrotic MMPs and their inhibitors (Hogg et al, 2004;Rennard, 2006;Salazar and Herrera, 2011;Churg et al, 2012;Jankowich and Rounds, 2012). Increases in the levels of alveolar macrophage-associated MMPs negatively correlate with forced expiratory volume in 1 s/forced vital capacity in COPD patients (Ishii et al, 2013). We have shown that depletion of macrophages by clodronate improves transpulmonary and airway resistance as well as dynamic compliance in experimental COPD (Beckett et al, 2013), which possibly occurs through the reduction in MMPs.…”
Section: Bjpmentioning
confidence: 99%
“…Ishii et al illustrated the inverse relationship of MMP12 mRNA expression levels in alveolar macrophages with a measure of airflow obstruction, the FEV 1 /FVC ratio. [35]…”
Section: Chromosome 11q22: Mmp12mentioning
confidence: 99%
“…Further molecular studies of the involved proteins might shed more light on this. We previously reported SNPs associated with CST3 mRNA and protein levels in alveolar macrophages 19. However, in the latter study, higher CST3 mRNA in alveolar macrophages was associated with higher FEV 1 .…”
Section: Discussionmentioning
confidence: 61%